Routing optimization method based on GPCR for vehicular Ad Hoc network - Zhiru GU; Min LI; Yonghong LONG; Xiaohua SHU; Qing RONG (Tongxin xuebao)
To improve the performance in sparse networks,local optimum,and routing loop in the greedy perimeter coordinator routing (GPCR) protocol,the weighted-GPCR (W-GPCR) protocol was proposed.The relationship between vehicle node routing and other parameters such as the Euclidean distance between node pairs,moving direction and density was profoundly analyzed,the composite parameter weighted model was established and the calculation method was designed for the existing routing problems,the weighted parameter ratio was selected adaptively in different scenarios,so as to obtain the optimal next-hop relay node.In order to verify the performance of the W-GPCR method,the proposed method was compared with the existing methods such as the traditional geographic perimeter stateless routing (GPSR) protocol,GPCR and so on,and the results show that the proposed method is superior to the package delivery ratio,end-to-end delay,and average hop count.